Manajemen Mutu Pendidikan Islam Berbasis TQM: Studi Moderasi Beragama di Pesantren Masyarakat Merapi Merbabu - Harefa, Fadhil Khalid; Usman, Nurodin (J-MPI (Jurnal Manajemen Pendidikan Islam), 2025)
This study aims to describe the quality management of Islamic education to develop religious moderation awareness in mountain communities. This study was conducted using a qualitative descriptive method approach. The location of this study was the Merapi Merbabu Community Islamic Boarding School. The theory used as an analytical tool is the total quality management or TQM theory which consists of three indicators, namely customer focus, continuous process improvement, and total involvement of all elements of management. Data collection techniques were carried out through interviews, observations, and documentation. The results of this study indicate that the Merapi Merbabu Community Islamic Boarding School has implemented TQM principles in implementing the quality of Islamic education and developing a religious moderation model. PM3 has established an activity plan that refers to customer satisfaction, implementation and improvement that are carried out continuously, and involves all stakeholders in every stage of management. The planning stage, implementation stage, and evaluation stage are carried out to realize the goals of a quality Islamic educational institution. By adhering to these TQM principles, PM3 has developed into an institution that not only produces graduates who excel in religious knowledge, but also becomes a moderation agent that is able to play a role in maintaining social harmony and diversity.